ANALISIS HUKUM TERHADAP TINDAK PIDANA PENYALAHGUNAAN NARKOTIKA OLEH PENGEDAR DAN PENGGUNA DITINJAU DARI UNDANG-UNDANG NOMOR 35 TAHUN 2009 TENTANG NARKOTIKA - Donny Alexander; Suhaidi Suhaidi; Tan Kamello; Mahmud Mulyadi (Universitas Sumatera Utara, 2018)
ABSTRACT Article 1, point 1 of Law No. 35/2000 on Narcotics states that narcotics is substance or drug which comes from plants or non-plants, either synthetic or semi-synthetic. Consuming narcotics can cause the decrease or change in consciousness, insensitivity, pain relief or no pain, and dependence. There are many types of narcotics as stipulated in Law No. 35/2009 on Narcotics in which there is tug-of-war between health approach and criminal approach so that it is interesting to see the legal position of narcotics users. It is difficult to find out the meaning of the expression, “narcotics user” as a subject (human being) in Law No.35/2009 since it uses many verbs. According to the Indonesian dictionary, the term, “user” is a person who uses something. When it is related to Article 1, point 1 of Law No. 35/2009 on Narcotics, it can be said that narcotics user is a person who uses substance or drug which comes from plants, either synthetic or semi-synthetic which can cause the decrease or change in consciousness, insensitivity, pain relief or no pain, and dependence. There are many types of narcotics as stipulated in Law No. 35/2009 on Narcotic. The term, “narcotics user” is used to make it easier for people to call a person who uses narcotics and to distinguish it from the grower, producer, distributor, courier, and dealer of narcotics. Keywords : Narcotics Abuse, Dealer and User, Law No. 35/2009 on Narcotics